Kejadian Hiperglikemia Baru Akibat Infeksi Covid-19 - Lukman Hakim Muttaqien; Yani Triyani; Wida Purbaningsih (Bandung Conference Series: Medical Science, 2023)
Abstract. Coronavirus disease (COVID-19) is an infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. The SARS-CoV-2 virus has a spike-like protein (S) structure, which will bind to the angiotensin converting enzyme 2 (ACE2) receptor. The number of tissues that express ACE2 receptors causes varied symptoms, ranging from mild symptoms such as coughing, to severe symptoms such as digestive disorders, heart failure, hypertension, and other systemic disorders such as hyperglycemia. So that there are many cases of increased blood sugar levels in COVID-19 patients which cause hyperglycemia. This study aims to determine the relationship between the incidence of new hyperglycemia and COVID-19. This study was conducted by taking medical record data at Al-Islam Hospital in the January-September 2021 period to obtain data on COVID-19 hospitalized patients and data on current blood sugar. This study used an analytical observational method with a case control design and the sampling technique was carried out using the total sampling method and analysis using the chi-square test. The medical record samples studied were 171 medical records at Al-Islam Bandung Hospital. The results showed that most of the subjects experienced hyperglycemia as many as 44 people (51.8%), and there was a significant relationship between COVID-19 infection and the incidence of hyperglycemia (P=0.038). COVID-19 infection is one of the causes of hyperglycemia. Abstrak. Penyakit Coronavirus (COVID-19) adalah penyakit infeksius yang disebabkan oleh virus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Virus SARS-CoV-2 memiliki struktur protein seperti spike protein (S), yang akan berikatan dengan reseptor angiotensin converting enzyme 2 (ACE2). Banyaknya jaringan yang mengekspresikan reseptor ACE2 menimbulkan gejala yang bervariasi, berawal dari gejala ringan seperti batuk, hingga gejala berat seperti gangguan pencernaan, gagal jantung, hipertensi, dan gangguan sistemik lain seperti hiperglikemia. Sehingga banyak kasus kenaikan kadar gula darah pada pasien COVID-19 yang menyebabkan hiperglikemia. Penelitian ini bertujuan untuk mengetahui hubungan antara kejadian hiperglikemia baru dengan COVID-19. Penelitian ini dilakukan dengan mengambil data rekam medis di RS Al-Islam pada periode Januari–September 2021 untuk mendapatkan data pasien rawat inap COVID-19 dan data gula darah sewaktu. Penelitian ini menggunakan metode observasional analitik dengan rancangan kasus control dan Teknik pengambilan sample dilakukan dengan metode total sampling serta analisis menggunakan uji chi-square. Sampel rekam medis yang diteliti sebanyak 171 rekam medis di RS Al-Islam Bandung. Hasil penelitian didapatkan Sebagian besar subjek mengalami hiperglikemia sebanyak 44 orang (51,8%), dan terdapat hubungan yang signifikan antara infeksi COVID-19 dengan kejadian hiperglikemia (P=0,038). Infeksi COVID-19 menjadi salah satu penyebab hiperglikemia.